Constraints on German diese demonstratives: language formality and subject-avoidance. Issue 1 (26th February 2020) - Patil, Umesh; Bosch, Peter; Hinterwimmer, Stefan
Abstract : Demonstrative pronouns in German occur in various paradigms such as die, diese, jene, diejenige, dieselbe, etc. Among these only the most frequent paradigm, die, has received attention from psycholinguistic research. In this paper, we investigate constraints on demonstrative pronouns from the diese paradigm. Diese-demonstratives are considered to be limited to formal language by native speakers, and in contemporary grammar they are assumed to prefer the most recent or the last mentioned antecedent. If these constraints really hold, diese-demonstratives seem to behave very differently from die-demonstratives which have been shown to prefer the antecedent that is not maximally prominent. We report three forced-choice experiments that test the constraints of language formality, order of mention and prominence through subjecthood. The results demonstrate that diese-demonstratives strongly prefer the formal language register as expected by native speakers. However, instead of the last mentioned antecedent, they prefer the antecedent that is non-prominent in terms of subjecthood which is similar to the preference that has been reported in the literature for die-demonstratives. We suggest that in a restricted context diese-demonstratives are formal counterparts of die-demonstratives.